Al-Al-Verbundguss mit höherfesten Knetlegierungen - Wedler, Jonathan; Schwankl, Matthias; Körner, Carolin (Giesserei, 2015)
In der hier beschriebenen Arbeit wurden Einlegeteile (Inserts) aus Aluminiumlegierungen der 2XXX- und 5XXX-Gruppe im Druckgießverfahren integriert. Ziel hierbei war die Erzeugung einer stoffschlüssigen Verbindung zwischen der Gussmatrix und dem Insert aus einer Knetlegierung, die normalerweise durch die natürliche Oxidschicht verlässlich verhindert wird. Zur Oberflächenaktivierung wurde die Aluminiumoxidschicht in einem vorgeschalteten Beizprozess entfernt und anschließend stromlos Zink abgeschieden. Eine anschließende Parameterstudie mit variierenden Tiegeltemperaturen und Gießkolbengeschwindigkeiten erlaubt einen Einblick in das Prozessfenster und die Bestimmung möglicher Einflussgrößen bei der Ausbildung einer Zink-Reaktionszone. Die gefertigten Verbundgussteile wurden anschließend auf ihre mechanischen Eigenschaften hin geprüft und die Grenzflächen hinsichtlich der Elementverteilung untersucht.

A process chain for integrating piezoelectric transducers into aluminum die castings to generate smart lightweight structures - Stein, Stefan; Wedler, Jonathan; Rhein, Sebastian; Schmidt, Michael; Körner, Carolin; Michaelis, Alexander; Gebhardt, Sylvia (Results in Physics, 2017)
The application of piezoelectric transducers to structural body parts of machines or vehicles enables the combination of passive mechanical components with sensor and actuator functions in one single structure. According to Herold et al. [1] and Staeves [2] this approach indicates significant potential regarding smart lightweight construction. To obtain the highest yield, the piezoelectric transducers need to be integrated into the flux of forces (load path) of load bearing structures. Application in a downstream process reduces yield and process efficiency during manufacturing and operation, due to the necessity of a subsequent process step of sensor/actuator application. The die casting process offers the possibility for integration of piezoelectric transducers into metal structures. Aluminum castings are particularly favorable due to their high quality and feasibility for high unit production at low cost (Brunhuber [3], Nogowizin [4]). Such molded aluminum parts with integrated piezoelectric transducers enable functions like active vibration damping, structural health monitoring or energy harvesting resulting in significant possibilities of weight reduction, which is an increasingly important driving force of automotive and aerospace industry (Klein [5], Siebenpfeiffer [6]) due to increasingly stringent environmental protection laws. In the scope of those developments, this paper focuses on the entire process chain enabling the generation of lightweight metal structures with sensor and actuator function, starting from the manufacturing of piezoelectric modules over electrical and mechanical bonding to the integration of such modules into aluminum (Al) matrices by die casting. To achieve this challenging goal, piezoceramic sensors/actuator modules, so-called LTCC/PZT modules (LPM) were developed, since ceramic based piezoelectric modules are more likely to withstand the thermal stress of about 700 °C introduced by the casting process (Flössel et al., [7]). The modules are made of low temperature cofired ceramic (LTCC) tapes with an embedded lead zirconate titanate (PZT) plate and are manufactured in multilayer technique. For joining conducting copper (Cu) wires with the electrode structure of the LPM, a novel laser drop on demand wire bonding method (LDB) is applied, which is based on the melting of a spherical CuSn12 braze preform with a liquidus temperature Tliquid of 989.9 °C (Deutsches Kupfer-Institut Düsseldorf, [8]) providing sufficient thermal stability for a subsequent casting process.
Keywords: Active noise reduction; Laser assisted wire bonding; Smart structures; Piezoelectric transducers; Die casting; Lightweight design

Sensor-based Observation and Numerical Simulation of Mold Filling During High Pressure Die Casting - Wedler, Jonathan; Körner, Carolin (Giesserei, 2019)
The die casting process is well established in the foundry industry. Nevertheless, there are still several challenges present, e.g. the entire control of mold filling. Detailed information about the filling level and the melt condition during the filling is highly favorable for optimizing both, the process and the quality of produced parts. The opacity of the mold in combination with short process times, high pressures and temperatures make the direct observation of the mold filling impossible. Numerical simulations help to visualize the melt flow as well as the thermal conditions during mold filling. However, on this way an assertion of the actual mold filling in the production of each casting is not possible. An opportunity to gather information of mold filling during the production process is to use suitable sensors which are directly positioned in the cavity. The present work analyzes opportunity of the observation of mold filling during high pressure die casting (HPDC) through the alignment of experimental sensor data and numerical results. The sensor data describe the level of mold filling during the casting cycle. This enables the depiction of the mold filling as a function of experimental process parameters such as process time, piston position, crucible temperature, dosing weight and thickness of the castings.<br

Wrought Al - Cast Al compound casting based on zincate treatment for aluminum wrought alloy inserts - Schwankl, Matthias; Wedler, Jonathan; Körner, Carolin (Journal of Materials Processing Technology, 2016)
The surface properties of solid inserts are critical to the development of a reaction zone in compound castings. In contrast to prior works (based on Al99.5) the goal of this paper is to apply the zincate treatment to different aluminum wrought alloys. This enables the possibility to create compound structures with enhanced mechanical properties. During zincate treatment the aluminum oxide layers are dissolved and a thin layer of zinc (<500 nm) prevents reoxidation. Coating parameters are optimized especially for compound castings: maximum coverage of the surface and high coating adhesion implemented by double zincate treatment. The pretreated inserts are embedded in an aluminum component by high pressure die casting. A sound metallic bonding between both aluminum alloys develops due to diffusion and reaction zones. Mechanical tests confirm a sound metallic bonding. Depending on the integrated wrought alloy enhanced mechanical properties of the compound structure can be achieved. Microprobe and fracture analysis provide detailed information about the interface properties of the compound structure, which can be enhanced by thermal treatment.
Keywords: Aluminum; Al–Al-compound; Casting; Compound casting; High pressure die casting; Wrought alloys; Zinc; Zincate treatment